Karakteristik Analisis Spektrofotometri IR Ekstrak Batang Kebiul (Caesalpinia bonduc (L.) Roxb) dengan Variasi Pelarut pada Maserasinya - Desy Amalia; Karina Primtyas; Septi Wulandry; Delta Baharyati (Jurnal Pharmacopoeia, 2026)
Caesalpinia bonduc (L.) Roxb is known to contain various secondary metabolites with antioxidant, anti-inflammatory, and antimicrobial properties. Differences in solvent polarity influence the types of compounds extracted; therefore, functional group profiling is essential to identify active constituents. This study aimed to compare the FTIR-ATR spectral profiles of C. bonduc stem extracts obtained using three solvents of different polarities: ethanol, ethyl acetate, and n-hexane. Extraction was carried out by maceration, and characterization was performed using a Bruker Alpha II FTIR spectrophotometer within the 4000–400 cm⁻¹ range. The ethanol extract exhibited strong absorption at 3430 cm⁻¹ (–OH) and 1635 cm⁻¹ (C=O), indicating polar compounds such as flavonoids and phenolics. The ethyl acetate extract showed distinctive bands at 1740 cm⁻¹ (C=O ester), while the n-hexane extract displayed peaks at 2922–2858 cm⁻¹ (C–H), associated with non-polar compounds such as fatty acids and terpenoids. Variations in absorption bands among the three extracts confirm that solvent polarity significantly affects the extracted chemical composition.This study demonstrates that differences in extraction solvents influence the composition of functional groups in the resulting chemical structures. Furthermore, the FTIR-ATR method has proven to be an effective technique for rapid and non-destructive characterization in identifying active compounds in medicinal plant extracts.